IMPACT OF BILOGIZATION ELEMENTS ON PRODUCTIVITY OF DARK CHESTNUT SOIL IN THE CONDITIONS OF DRY STEPPE ZONE - Gumarova, Zh. M. (Западно-Казахстанский аграрно-технический университет имени Жангир хана, 2015)
The research on improving crop yields and increasing isolation cycle of matter and energy in agro-ecosystems based on natural reproduction of soil fertility through the use elements of biological function as a mulch of straw, manure compost humus showed the best conditions and increased soil biological activity
Keywords: biologization; natural reproduction; soil fertility; humification.; почвоведение; навозный компост; гумусообразование; периодическое издание; научный журнал; отечественное издание